Diode laser and white lesions: A clinical study on postoperative recovery, depth control and wound healing - Nilesh Raval; D Rama Raju; Appaji Athota; T Y Reddy (Wolters Kluwer Medknow Publications, 2011)
Laser dentistry has always been a subject of interest. Among hard and soft tissue lasers, the latter finds much more acceptance in terms of clinical applications. Diode lasers have found much acceptance in all the branches of dentistry. Compact size and financially viable-diode laser has become a big practice enchancer tool. The difference in contact and noncontact mode in treating white lesions, in terms of various clinical parameters has been discussed.